2018
DOI: 10.1113/jp276935
|View full text |Cite
|
Sign up to set email alerts
|

The central amygdala to periaqueductal gray pathway comprises intrinsically distinct neurons differentially affected in a model of inflammatory pain

Abstract: Key points The central nucleus of the amygdala (CeA) encompasses the main output pathways of the amygdala, a temporal lobe structure essential in affective and cognitive dimensions of pain. A major population of neurons in the CeA send projections to the periaqueductal gray (PAG), a key midbrain structure that mediates coping strategies in response to threat or stress. CeA‐PAG neurons are topographically organized based on their targeted subregion within the PAG. PAG‐projecting neurons in the central medial (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
51
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(60 citation statements)
references
References 58 publications
6
51
0
1
Order By: Relevance
“…Together, our results 32 identify fundamentally important distinguishing features of PKCδ + and Som + cells that support cell-33 type-specific function in the CeA. 34 35 Keywords: central amygdala, Somatostatin, protein kinase C delta, intrinsic excitability, 36 morphology, neuropathic pain 37 2002, Chieng et al, 2006, Schiess et al, 1999, Li and Sheets, 2018. Recent studies have further 64 shown that CeLC neurons with different firing properties are topographically organized based on 65 their projection targets (Li and Sheets, 2018), suggesting that heterogeneity of function within the 66 CeLC might also be anatomically defined.…”
mentioning
confidence: 76%
“…Together, our results 32 identify fundamentally important distinguishing features of PKCδ + and Som + cells that support cell-33 type-specific function in the CeA. 34 35 Keywords: central amygdala, Somatostatin, protein kinase C delta, intrinsic excitability, 36 morphology, neuropathic pain 37 2002, Chieng et al, 2006, Schiess et al, 1999, Li and Sheets, 2018. Recent studies have further 64 shown that CeLC neurons with different firing properties are topographically organized based on 65 their projection targets (Li and Sheets, 2018), suggesting that heterogeneity of function within the 66 CeLC might also be anatomically defined.…”
mentioning
confidence: 76%
“…To acclimatize mice to the test procedure, they were placed in the containers for 45 min prior to each test session. A set of eight calibrated von Frey filaments ranging from 0.008 to 6 g (North Coast Medical, Morgan Hill, CA, USA) were applied alternately to the plantar surface of each hind paw until they bent (Li and Sheets, 2018). The duration of each stimulus was approximately 1 s and nociceptive behaviors were considered to be retraction/lifting, rapid shaking, and/or licking of the hind paw.…”
Section: Von Frey Testmentioning
confidence: 99%
“…Особую роль для развития СВА играет взаимодействие между амигдалой и ЦСВСМ (Kim et al 2013;Li, Sheets 2018). Основой для этого взаимодействия выступают КРФ сигнальные пути, вовлекающиеся в регуляцию болевой чувствительности.…”
Section: центральные механизмы стресс-вызванной анальгезии: участие кunclassified